2013
DOI: 10.1093/geront/gnt129
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Organizational Culture in Retaining Nursing Workforce

Abstract: Organizational culture had differential effects on the turnover of RN, LPN, and NA staff that should be addressed in developing culture-change strategies. More flexible organizational culture values were important for LPN staff only, whereas unexpectedly, greater emphasis on rigid internal rules helped facilities retain RNs. Facilities with a stronger focus on customer needs had higher turnover among all staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 27 publications
2
53
1
1
Order By: Relevance
“…Psychological empowerment and its components can be affected by distinct types of organizations and the educational culture . In nursing, research on organizational culture primarily focused on the nature of organizational culture in health care management and health care quality; the impact of organizational culture on health care practitioners’ behaviors, job satisfaction, turnover, and intention to stay; and the effect of organizational culture on nursing professionalism . On the other hand, the research on psychological empowerment mainly focused on the structural and psychological empowerment of nurse practitioners and practicing nurses, and nursing students’ empowerment during clinical practice and education …”
Section: Introductionmentioning
confidence: 99%
“…Psychological empowerment and its components can be affected by distinct types of organizations and the educational culture . In nursing, research on organizational culture primarily focused on the nature of organizational culture in health care management and health care quality; the impact of organizational culture on health care practitioners’ behaviors, job satisfaction, turnover, and intention to stay; and the effect of organizational culture on nursing professionalism . On the other hand, the research on psychological empowerment mainly focused on the structural and psychological empowerment of nurse practitioners and practicing nurses, and nursing students’ empowerment during clinical practice and education …”
Section: Introductionmentioning
confidence: 99%
“…12 Recent examples include studies that have investigated the role of organizational culture on a patient safety culture, 20 long-term hospital performance, 21 an improvement in processes (specifically hand washing frequency), and outcomes (vancomycin-resistant enterococci incidence), 22 and nursing turnover. 23 Studies that have evaluated the influence of the work environment on patient outcomes have reported that nurse staffing, 24,25 nursing skill mix, 26,27 nurse education levels, 28 working conditions and level of burnout, 24,2830 along with employing intensivists in ICUs, 31 and high levels of relational coordination, 32 have been positively associated with patient outcomes in some studies. Lastly, the influence of a positive safety climate has been studied for its relationship to nurse and patient outcomes, 3336 but the findings are inconsistent at this time.…”
Section: Previous Researchmentioning
confidence: 99%
“…[1,[4][5][6] Various factors attributed to nursing turnover include: job satisfaction, orga-nizational commitment, poor quality of work life, organizational culture, job stress, long working hours, burnout, and work-family conflict. [4][5][6][7] Organizational culture shapes employees' behaviors, promotes values relevant to the strategic foci of the organization, and determines the way work is done. [3,7] Organizational culture influences leadership style, leadership behaviour and RN job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Organizational culture shapes employees' behaviors, promotes values relevant to the strategic foci of the organization, and determines the way work is done. [3,7] Organizational culture influences leadership style, leadership behaviour and RN job satisfaction. [8] Leadership behaviour influences job satisfaction, since job satisfaction has been associated with nurses who perceive their managers to be supportive and caring.…”
Section: Introductionmentioning
confidence: 99%